Curation in Education: Implications for Adult Educators in Teaching and Research - Catherine A Cherrstrom; Carrie Boden (Adult Education Research Conference, 2019)
This systematic and integrative literature review examined curation in education with implications for adult educators in teaching and research and adult students in learning.
Keywords: curation; higher education; teaching; learning; research